TIM3 and TIGIT-expressing CD4 T cells are impacted by kidney transplantation and associated with risk of infection - Pickering, Harry; Sen, Subha; Cappelletti, Monica; Lum, Erik L.; Bunnapradist, Suphamai; Reed, Elaine F.; Schaenman, Joanna M. (Frontiers in Immunology, 2025)
IntroductionOlder kidney transplant patients experience higher rates of infection compared with younger transplant patients suggesting the impact of age-associated immune dysfunction. However, little is known about the impact of immunosuppression including antithymocyte globulin (ATG) induction, as well as whether T cell subtypes can predict risk for infection.MethodsWe collected blood from 91 patients before and then 3 months after kidney transplantation and analyzed CD4 and CD8 T cell phenotypes to determine the impact of immunosuppression on immune maturation, senescence, and infection.ResultsAfter transplantation the number of naïve T cells decreased overall, while TIM3-expressing naïve and central memory (CM) CD4 T cell frequency increased, with more striking change in patients receiving ATG compared with basiliximab induction. Transplantation also led to increased frequency of TIGIT-expressing effector memory (EM) CD4 T cells and senescent TIGIT and KLRG1-expressing CD8 T cells. Decreased frequencies of naïve CD4 and CD8 T cells (p=0.016 and p=0.038, respectively) and increased frequency of CD4 CM and EM TIGIT+ T cells (p=0.022) were associated with development of infection. A model incorporating increased frequency CD4 EM TIGIT+ T cells and ATG induction was predictive of development of infection after kidney transplantation (HR 3.73, CI 1.08-12.9).DiscussionIncreased frequency of TIM3 and TIGIT markers associated with T cell experience and senescence was a notable phenotypic change associated with transplantation and induction and maintenance immunosuppression. Incorporation of TIGIT expression and induction type into an infection prediction model holds promise for risk stratification and individualization of immunosuppression to decrease risk of adverse outcomes, especially for older patients.